(untitled) (GEOgraphia, 2009)
Este artigo busca questionar a forma em que a convergência entre território, mercado e Estado se desenvolveu no continente europeu até chegar aos territórios coloniais, especialmente a América Latina. Abstract: This paper aims to discuss the way by which convergence among territory, market and State have been developed in Europe, until reach colonial territories, specially Latin America.